2001
DOI: 10.3189/172756401781818455
|View full text |Cite
|
Sign up to set email alerts
|

The Laptev Sea flaw polynya, Russian Arctic: effects on the mesoscale hydrography

Abstract: A detailed analysis of hydrographic data from a period of 20 years (1980−99) has shown that the persistent presence of a flaw polynya influences mesoscale hydrography of the Laptev Sea, Russian Arctic. Based on these data, the interannual variability of surface water salinity within the polynya has been estimated. As the salinity increase in the surface water layer is mainly caused by the formation of new ice within the polynya, the average ice-production rate of the polynya was calculated. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In addition, openings in the pack ice that form during winter are sites of brine formation, affecting the local convection and water mass stratification (Dmitrenko et al, 2001). The wind-driven polynyas result in intense heat loss from the ocean to the atmosphere, controlling the formation of fog banks and low-level clouds (Arctic stratus).…”
Section: General Sea-ice Regimementioning
confidence: 99%
“…In addition, openings in the pack ice that form during winter are sites of brine formation, affecting the local convection and water mass stratification (Dmitrenko et al, 2001). The wind-driven polynyas result in intense heat loss from the ocean to the atmosphere, controlling the formation of fog banks and low-level clouds (Arctic stratus).…”
Section: General Sea-ice Regimementioning
confidence: 99%
“…The flaw polynyas in the Russian Arctic are caused by continuous southerly winds, which keep large areas off the fastice edge open (Zakharov, 1997). The polynya in the Laptev Sea is an important factor for the hydrography during winter (Dmitrenko et al, 2001a). It causes the formation of a cellular circulation with stable underice surface currents directed to the open water and counter currents below the pycnocline in the bottom layer because of brine rejection during ice formation (Dmitrenko et al, 2001a).…”
Section: Sediment Dynamics Beneath the Polynyamentioning
confidence: 99%
“…The rate of salinity adjustment in response to ice formation was evaluated statistically from time series of winter salinity observations. These results evidence that, for instance, in the eastern Laptev Sea polynya, the mean salinity increase of the surface layer can reach up to 4 units, corresponding to an ice production of 3 to 4 m [Dmitrenko et al, 2001]. Therefore, it was confirmed that the Laptev Sea polynya is an important ice source for the Transpolar Drift system.…”
Section: Riverine Dischargementioning
confidence: 60%
“…The increased winddriven advection of ice away from the Laptev Sea coast when the Arctic Oscillation (AO) is positive implies enhanced coastal polynya production and brine release into the shelf water. When the AO is negative, the ice production and seasonal salinity amplitude tends to weaken [Dmitrenko et al, 2001]. …”
Section: Riverine Dischargementioning
confidence: 99%